(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the impact of knowledge management on the organizational creativity of employees within the Investor Services Center in Makkah Al-Mukarramah, and to identify previous research and studies related to knowledge management and organizational creativity. And finally, the results and recommendations of the study In order to achieve the objectives of the study, the questionnaire was used as a tool for collecting data from the employees within the Investors Services Center in Makkah Al-Mukarramah, whose number is (23) employees, including three managers. Knowledge has a positive effect on organizational performance and behavior, which increases the process of organizational creativity within the Investor Services Center, and that knowledge management leads to increased organizational loyalty to the abundance of information that employees need, and that knowledge management allows employees to work on exchanging experiences with experienced people to gain knowledge and acquire new knowledge to develop themselves professionally, as well as providing employees with the appropriate environment for exchanging knowledge with each other, and dealing with technological means in disseminating knowledge, The study recommended the necessity of providing effective and modern means of communication for the application of knowledge management within the Investors Services Center in Makkah Al-Mukarramah, encouraging senior management of employees to participate in the transfer of knowledge and expertise, and establishing knowledge management units within the Investors Services Center similar to the Crisis Management Unit.